Pengaruh Resistance Training Terhadap Penurunan Gula Darah Pasien Diabetes Melitus Tipe 2 : Literature Review - Larasati, Diah; Suriadi, Suriadi (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2025)
Resistance training is a frequently recommended form of physical exercise for individuals with diabetes mellitus. The objective of this study was to investigate the effect of resistance training on the reduction of blood glucose levels in patients with type 2 diabetes mellitus. A systematic literature review was conducted by searching the PubMed and Google Scholar databases using predefined keywords. Following the application of inclusion and exclusion criteria, five relevant articles were selected for analysis. The review revealed significant evidence supporting the effectiveness of resistance training in lowering blood glucose concentrations among this patient population. These findings highlight the potential of resistance training as a viable non-pharmacological intervention for managing type 2 diabetes; however, further research is warranted to comprehensively assess its long-term impact on glycemic regulation.